A Survey on Sufficient Conditions for Hamiltonian Cycles in Bipartite Digraphs - Ge, Huifen; Zhang, Shumin; Ye, Chengfu (Discontinuity, Nonlinearity, and Complexity, 2026)
A digraph D=(V,A) is called a bipartite digraph if there exists a partition (X,Y) of V(D) into two partite sets such that every arc of D has its end-vertices in different partite sets. It is called balanced if |X| = |Y|. If a digraph D has a directed cycle C which covers all of its vertices, then D is Hamiltonian. This paper mainly introduces some sufficient conditions for Hamiltonian cycles in balanced bipartite digraph.